Job stress dimensions and their relationship to general health status in nurses - M Barzideh; A Choobineh; SH Tabatabaei (طب کار)
Background: There is little data available on job stress dimensions and their relationship to general health status among Iranian nurses. The aims of this study were investigating job stress dimensions and examining their relationship to general health status among nurses working in the hospitals of Shiraz University of Medical Sciences (SUMS). Methods: In this cross-sectional study, 385 randomly selected nurses of SUMS were assessed. The Persian version of Job Content Questionnaire (P-JCQ), the Persian version of General Health Questionnaire (GHQ-28) and demographic questionnaires were used for data collection. Using SPSS (version 11.5) software, descriptive statistics and Mann-Whitney U test were applied for data analysis. Results: The means (SD) of decision latitude, psychological job demands, social support, physical job demands and job insecurity were found to be 58.15(6.50), 38.19(5.14), 22.67(3.67), 16.03(2.58) and 7.74(3.85), respectively. The results revealed that decision latitude and social support dimensions had low levels, but psychological and physical job demands as well as job insecurity dimensions had high levels among the study subjects. The mean (SD) total score of GHQ-28 was found to be 28.34(12.93) which was higher than the cut-off point value of 23. Based on the results of GHQ-28, 35.3% and 64.7% of the nurses were categorized as healthy and suspected health disorders groups, respectively. The mean score of all job stress dimensions had significant relationship with general health status. Conclusion: In the majority of cases, subjects were exposed to high levels of job stress. Most of nurses were suspected to suffer from some kind of health disorders. Based on the results, any interventional program for health disorders prevention should focus on reducing job insecurity as well as increasing decision latitudes (control) and social support (from both co-workers and supervisors) among nurses.